A catalogue of the geophilomorph centipedes (Chilopoda) from Central and South America including Mexico - Foddai, Donatella (2000)
This paper is an annotated catalogue of the gcophilomorph centipedes known from Mexico, Central America, West Indies, South America and the adjacent islands. 310 species and 4 subspecies in 91 genera in II fami lies are l isted, not including 6 additional taxa of uncertain generic identity and 4 undescribed species provisionally listed as 'n.sp.' under their respective genera. Sixteen new combinations are proposed: GaJTina pujola (CHAMBERLIN, 1 943) and G. vera (CHAMBERLIN, 1 943), both from Pycnona; Nesidiphilus plusioporus (A TTEMS, 1 947). from Mesogeophilus VERHOEFF, 1 90 I; Po/ycricus bredini (CRABILL, 1 960), P. cordobanensis (VERHOEFF. 1 934), P. haitiensis (CHAMBERLIN, 1915) and P. nesiotes (CHAMBERLIN. 191 5), all from Lestophilus; Tuoba baeckstroemi (VERHOEFF, 1 924), from Geophilus ( Nesogeophilus); T. culebrae (SILVESTRI. 1 908), from Geophilus; T. latico/lis (A TTEMS, 1 903), from Geophilus ( Nesogeophilus); Titanophilus hasei (VERHOEFF, 1 938), from Notiphilides ( Venezuelides); T. incus (CHAMBERLIN, 1 941 ), from lncorya; Schendylops nealotus (CHAMBERLIN. 1 950), from Nesondyla nealota; Diplethmus porosus (ATTEM S, 1 947). from Cyclorya porosa; Chomatohius craterus (CHAMBERLIN, 1 944) and Ch. orizabae (CHAMBERLIN, 1 944), both from Gosiphilus. The new replacement name Schizonampa Iibera is proposed pro Schizonampa prognatha (CRABILL. 1 964) ex Schizolaenia prognatha CRABILL, 1 964 nee Schizotaenia prognatha COOK. 1 896. Fourteen new combinations are proposed: Nesidiphilus plusioporus (Attems, 1947), from Mesogeophilus Verhoeff, 1901; Polycricus bredini (Crabill, 1960), P. cordobanensis (Verhoeff, 1934), P. haitiensis (Chamberlin, 1915) and P. nesiotes (Chamberlin, 1915), all from Lestophilus; Tuoba baeckstroemi (Verhoeff, 1924), from Geophilus (Nesogeophilus); T. culebrae (SILVESTRI, 1908), from Geophilus; T. laticollis (Attems, 1903), from Geophilus (Nesogeophilus); Titanophilus hasei (Verhoeff, 1938), from Notiphilides (Venezuelides); T. incus (Chamberlin, 1941), from Incorya; Schendylops nealotus (Chamberlin, 1950), from Nesondyla nealota; Diplethmus porosus (Attems, 1947), from Ciclorya porosa; Chomatobius craterus (Chamberlin, 1944) and Ch. orizabae (Chamberlin, 1944), both from Gosiphilus. The new replacement name Schizonampa libera is proposed pro Schizonampa prognatha (Crabill, 1964) ex Schizotaenia prognatha Crabill, 1964 nec Schizotaenia prognatha Cook, 1896.